Odpowiedzi

2009-12-29T15:12:31+01:00
(x-5)²-3*(x-1)(x+1)-(2x²-1)+x(2x-3)=x²-10x+25 -3x² +3-2x²+1+2x²-3x=-2x²-13x+29

(4+x)(4-x)-2x(1-3x)+2(x+2)²-4(x²-1)=16-x²-2x+6x²+2x²+4x+4-4x²+4=3x²+2x+8
2009-12-29T19:19:24+01:00
(x-5)²-3(x-1)(x+1)-(2x²-1)+x(2x-3)= x²-10x+25-3x²+3-2x²+1+2x²-3x= -2x²-13x+29

(4+x)(4-x)-2x(1-3x)+2(x+2)²-4(x²-1)= 16-x²-2x+6x²+2x²+8x+8-4x²+4=3x²+6x+28
Najlepsza Odpowiedź!
2009-12-29T19:26:20+01:00
(x-5)²-3*(x-1)(x+1)-(2x²-1)+x(2x-3)=x²-10x+25 -3x² +3-2x²+1+2x²-3x=-2x²-13x+29

(4+x)(4-x)-2x(1-3x)+2(x+2)²-4(x²-1)= 16-x²-2x+6x²+2x²+8x+8-4x²+4=3x²+6x+28

^^